Control and translocation of saflufenacil in fleabane (Conyza spp.) according to plant integrity - Bruno Mussoi Cavichioli (Revista Facultad Nacional de Agronomía - Medellín, 2021)
Efficient herbicide absorption and translocation, and satisfactory weed control can be affected by the site of herbicide application. However, during harvesting of crops of previous soybean sowing, the cutting process made by harvesters on the fleabane may generate a difficult management in pre-sowing of the crop by limiting the leaf area of the absorption of the herbicide. Experiments were conducted to evaluate the control efficiency and translocation potential of saflufenacil in fleabane plants with different leaf and stem conditions. Experiment I was arranged in a 2x10 factorial scheme, with factor A corresponding to leaf integrity, and factor B corresponding to different levels of injury and saflufenacil application. Weed control was evaluated at 7, 14, and 21 days after herbicide treatment (DAT), and dry matter was evaluated at 21 DAT. Experiment II consisted of applying saflufenacil to different fleabane structures, where the percentage of necrotic area was evaluated at 1, 3, 5, and 7 DAT. Fleabane control was higher than 75% in all treatments with saflufenacil application, with greater control in plants previously defoliated. Saflufenacil application on 10 and 20 cm hairy fleabane plants was also efficient in all treatments. Saflufenacil application in old stem showed a larger necrotic area, while application in the site of the cutting resulted in a lower necrotic area. The main pathway for translocation of saflufenacil is via xylem and the stem proved to be the absorption element of the herbicide when leaf area is limited.